2012
DOI: 10.5301/ijao.5000126
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of persistent intradialytic hypertension in a hemodialysis population with extended follow-up

Abstract: Intradialytic hypertension is a persistent phenomenon in a subset of hemodialysis patients. Ultrafiltration rate was the only volume-related variable that differed between patients with and without persistent intradialytic hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 13 publications
5
45
2
1
Order By: Relevance
“…We previously showed that an increase in systolic BP ≥10 mmHg from pre- to post-dialysis occurred at least once in almost all patients in a 350 patient cohort followed for six months, and we have also defined the expected frequency for IH to occur within a dialysis population [6]. Our IH patients in this study (systolic BP increase of at least 10 mmHg from pre- to post-hemodialysis in >40% of treatments over prior 6 months) experienced IH as frequently as the 80 th –90 th percentile from our prior study [6]; and our controls in this study (systolic BP increase of at least 10 mmHg from pre- to post-hemodialysis in 11% of treatments over prior 6 months) experienced IH as frequently as the 25 th –30 th percentile from our prior study [6]. Our current study’s methodology clearly minimizes the risk of misclassification bias and is highly applicable to patients with recurrent IH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously showed that an increase in systolic BP ≥10 mmHg from pre- to post-dialysis occurred at least once in almost all patients in a 350 patient cohort followed for six months, and we have also defined the expected frequency for IH to occur within a dialysis population [6]. Our IH patients in this study (systolic BP increase of at least 10 mmHg from pre- to post-hemodialysis in >40% of treatments over prior 6 months) experienced IH as frequently as the 80 th –90 th percentile from our prior study [6]; and our controls in this study (systolic BP increase of at least 10 mmHg from pre- to post-hemodialysis in 11% of treatments over prior 6 months) experienced IH as frequently as the 25 th –30 th percentile from our prior study [6]. Our current study’s methodology clearly minimizes the risk of misclassification bias and is highly applicable to patients with recurrent IH.…”
Section: Discussionmentioning
confidence: 99%
“…Most hemodialysis patients experience IH in a small percentage of their dialysis treatments, but IH is a persistent and recurrent phenomenon in some hemodialysis patients [6]. Understanding the pathophysiology of IH is important because patients with recurrent IH have higher ambulatory BP burden [7, 8] and increased risk for morbidity and mortality [5, 911].…”
Section: Introductionmentioning
confidence: 99%
“…One recent cohort study defined intradialytic hypertension as an increase in systolic BP ≥10 mmHg from pre to post dialysis to identify the prevalence of this phenomenon over long term follow up. Over the course of 6 months, intradialytic hypertension occurred in over 90% of the patients at least once 7 . The median percentage of treatments where intradialytic hypertension occurred during that 6 month period in this cohort was 18% such that half the subjects experienced intradialytic hypertension in 18% of the treatments or less, and half experienced intradialytic hypertension in 18% or more of their treatments.…”
Section: Epidemiologymentioning
confidence: 99%
“…[52,53] The prevalence of intradialytic hypertension ranges 5–15% among maintenance HD patients, depending on the definition. [54,55] Currently, there is no universally accepted definition of intradialytic hypertension. It is typically defined as BP increase during or immediately after HD, resulting in post-HD BP >130/80 mmHg, the KDOQI hypertension threshold.…”
Section: Intradialytic Blood Pressure Risementioning
confidence: 99%